Technostress in Libraries and the Development of Technology in Dynamic Library - Kristyanto, Dian (Universitas Pendidikan Indonesia, 2021)
This study aims to explain technostress disturbances in librarians due to technological developments in libraries that are too dynamic, as well as other challenges in the form of librarian readiness in facing the times. This study also uses the literature study method by reviewing relevant literature sources such as books, printed scientific journals, and electronic versions, as well as selected online information sources. The results of this study explain that technostress disturbances in librarians can be seen from five dimensions, namely techno-overload, techno-investment, techno-complexity, techno-insecurity, and techno-uncertainty. Technological developments in the library can be seen in the new challenges for librarians who require new skills in the field of technology, among others; integrated library systems, emerging web technology, electronic resource management, web page development, institutional repositories, and database management. The benefit of this study is librarians need to regulate the rhythm of work by increasing competence in the field of information technology and addressing the development of information technology wisely as an opportunity to improve the quality of library services in the future.